Financing and Delivery of Urban Services in the Philippines: An Overview - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 1998)
Just as urbanization has its advantages, it also has a number of problems like pollution, insufficient sanitation facility and inadequate provision of social services. This is normally resolved either through the imposition of rural-urban migration control or through the efficient management and financing of the urban sector. This paper deals with the latter focusing on financing and delivery of urban social services. This also assesses the determinants of revenue performance of city local government units (CLGU's) and determinants of CLGU's expenditures for the years 1991-1995. Various measures to close the urban fiscal gap are suggested.
Keywords: 330; urban management; urbanization